Cost-Effectiveness of a Program to Eliminate Disparities in Pneumococcal Vaccination Rates in Elderly Minority Populations: An Exploratory Analysis - Michaelidis, Constantinos I. (2013)
OBJECTIVE: Invasive pneumococcal disease is a major cause of preventable morbidity and mortality in the United States, particularly among the elderly (>65 years). There are large racial disparities in pneumococcal vaccination rates in this population. Here, we estimate the cost-effectiveness of a hypothetical national vaccination intervention program designed to eliminate racial disparities in pneumococcal vaccination in the elderly. METHODS: In an exploratory analysis, a Markov decision-analysis model was developed, taking a societal perspective and assuming a 1-year cycle length, 10-year vaccination program duration, and lifetime time horizon. In the base-case analysis, it was conservatively assumed that vaccination program promotion costs were $10 per targeted minority elder per year, regardless of prior vaccination status and resulted in the elderly African American and Hispanic pneumococcal vaccination rate matching the elderly Caucasian vaccination rate (65%) in year 10 of the program. RESULTS: The incremental cost-effectiveness of the vaccination program relative to no program was $45,161 per quality-adjusted life-year gained in the base-case analysis. In probabilistic sensitivity analyses, the likelihood of the vaccination program being cost-effective at willingness-to-pay thresholds of $50,000 and $100,000 per quality-adjusted life-year gained was 64% and 100%, respectively. CONCLUSIONS: In a conservative analysis biased against the vaccination program, a national vaccination intervention program to ameliorate racial disparities in pneumococcal vaccination would be cost-effective.